Sexuality Assessment in Women Diagnosed with Ovarian Cancer - Patricio Jaramillo Guerrero; Edison Enrique Sotalin Nivela; Eduardo Leonel Alvarado Pico (Revista Finlay)
Foundation: sexual life disorders can negatively affect self-esteem and social relationships, especially in patients undergoing gynecological surgery and oncological treatment. Objective: to evaluate sexuality in women diagnosed with ovarian cancer, with central interest in changes in sexual function, sexual desire, sexual satisfaction and sexual problems related to the disease and its treatment. Method: a descriptive and correlational, longitudinal and retrospective study was carried out that covered the period from 2018 to 2021. The population under study were female patients from the gynecological outpatient clinics of a private hospital. A total of 187 patients were included as study objects. The sample corresponded to the universe. The fundamental technique for data collection was the questionnaire. Several anonymous and voluntary instruments were applied: Sexual Satisfaction Questionnaire, Beck Depression Scale and Sense of Quality of Life Questionnaire. Nominal qualitative variables were defined to establish sociodemographic characteristics (age, sex, marital status, educational level, race and occupational level) and quantitative variables to define the attributes of the members according to their situation before treatment (time elapsed since diagnosis and amount according to type of treatment). The data obtained were subjected to statistical analysis, including correlation calculations using Cramer's V coefficient. Results: a relationship was found between sexual satisfaction and all areas of quality of life in patients undergoing oncological treatment. The strongest relationship was with the subjective sphere of the patients. A significant association was also observed between the absence of depressive symptoms and sexual satisfaction, in addition, a significant deterioration in sexual satisfaction in patients undergoing chemotherapy. Conclusions: the significant impact of depression on sexual satisfaction supports the need to address depressive symptoms to improve patients' sexual sphere. The inclusion of a psycho-oncologist in the healthcare system could contribute to a faster recovery of patients in their normal sexual life.